Mergers, managerial incentives, and efficiencies - Dragan Jovanovic (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We analyze the effects of synergies from horizontal mergers in a Cournot oligopoly where principals provide their agents with incentives to cut marginal costs prior to choosing output. We stress that synergies come at a cost which possibly leads to a countervailing incentive effect: The merged firm's principal may be induced to stifle managerial incentives in order to reduce her agency costs. Whenever this incentive effect dominates the well-known direct synergy effect, synergies actually reduce consumer surplus which opposes the use of an efficiency defense in merger control.
Keywords: D21; D86; L22; L41; 330; Managerial Incentives; Horizontal Mergers; Merger Control; Productive Efficiency Gains; Synergies; Efficiency Defense